PERAN STAKEHOLDER DALAM PENGELOLAAN KAWASAN KONSERVASI MANGROVE DAN KEPITING (KKMK) KOTA TARAKAN - Yulma, Yulma; Kustanti, Asihing; Soemarno, Soemarno; Mahmudi, Mohammad (Universitas Mataram, 2025)
Mangrove ecosystem management in the Mangrove and Crab Conservation Area (KKMK) requires active collaboration from various stakeholders to achieve ecological and socio-economic sustainability. The research objective is to identify and explain the role of each stakeholder in the sustainability of KKMK management. The method used in this research is descriptive quantitative by collecting data and information through observation, interviews, and documentation. The results showed that there are 15 parties involved in the management of KKMK, and the role of each stakeholder is divided into four quadrants, namely the subject quadrant occupied by community groups consisting of Baya Damo Laid (BDL), fish fishermen, and crab fishermen, the key players quadrant occupied by the City Government, DPRKKP, DLH, PUPR, BPN, and Polres, the context setter quadrant occupied by Pertamina, PLN, and BPKIM, and the crowd quadrant occupied by Tarakan Tengah Village, KPH, and DKP.